PENGEMBANGAN MATERI AJAR MENULIS NASKAH DRAMA BERBANTUAN MEDIA KOMIK STRIP DIGITAL PADA SISWA SMA - Sihaloho, Bonifa Imelda; Harahap, Rosmawaty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop teaching materials for writing drama scripts assisted by digital comic strip media for eleventh-grade high school students. This research employed the Research and Development (R&D) method using the ADDIE model, which was limited to the stages of analysis, design, and development. The study was conducted at SMA Negeri 19 Medan with the subjects consisting of students from class XI-1. Data collection techniques included observation, interviews, questionnaires, and documentation. The developed product was validated by material experts and media experts. The results showed that the material expert validation obtained a percentage of 84% and the media expert validation obtained 81.33%, both categorized as highly feasible. The average validation result from both experts reached 82.67%. In addition, student responses obtained a percentage of 84.93% with a very good category. Therefore, the teaching materials assisted by digital comic strip media are considered suitable for use in learning drama script writing for eleventh-grade high school students.